DISTRIBUSI VERTIKAL GASTROPODA PADA MANGROVE Rhizophora apiculata DI TELUK KENDARI - Muhsin Muhsin; Jamili Jamili; Hendra Hendra (BioWallacea : Jurnal Penelitian Biologi (Journal of Biological Research), 2016)
ABSTRACTThe aim of this study was to know the vertical distribution of gastropoda at the mangrove Rhizophora apiculata in the Kendari Beach. Method whice isusingin research is transect line. The six transects lines and 20 quadrates 20x20 m for tree, 10x10 m for pole, 5x5 m for boundary pole, ang 2x2 m for seedling. Two samplings of mangrove tree, pole, boundary pole and seedling were chosen each quadrat for observation. The numbers of species and individuals of gastropods were counted in each organ of mangrove samplings (roots, stems, and leaves organs). The parameters of vertical distrubution of gastropods were analyzed including frequency and abundance. The results of this study showed that there exists 8 species of gastropods at the mangrove samplings in Kendari Beach, where seven species found at site I and III, whereas six in found at site II. Species of Littorina scabra showed as the heighest frequency value at all site is 0,75. Therefore, the Littorina scabra are the common snails in this region, bacause they were found at all site in Kendari Beach. The abundance of gastropods in the mangrove sampling was found to be high at roots and has the lowest at leaves. The species of Littorina scabra at all vegetative organs of mangrove samplings in the Kendari Beach and suggesting is widest distribution.Keywords : Gastropods, Abundance, Vertical Distribution, Bay of Kendari.